Method as funds projects professional samorealyzatsyy senior school teacher - Кіриченко, С. В. (Scientific notes of the pedagogical department, 2017)
In essence article theoretically obosnovano obrazovatelnoy activities proektyrovochnoy teacher as the process of obtaining obrazovatelnoho product, trebuet kachestven known and professional skills samorealyzatsyy in the planning, neposredstvenno perform teaching of action on tvorcheskom level, organization and cooperation affiliates relations. Proved, something method javljaetsja funds projects professional samorealyzatsyy senior teacher school. Established method Using something in projects working with senior classes uchaschymysya positively to vlyyaet professional samoopredelenye, selforganization, cooperation.